Inequalities in Financial Distress, Symptoms, and Quality of Life Among Patients with Advanced Cancer in France and the U.S. (15th March 2019) - Barbaret, Cécile; Delgado‐Guay, Marvin O.; Sanchez, Stéphane; Brosse, Christelle; Ruer, Murielle; Rhondali, Wadih; Monsarrat, Léa; Michaud, Patrick; Schott, Anne Marie; Bruera, Eduardo; Filbet, Marilène
Abstract: Background: Financial distress (FD) is common among patients with advanced cancer. Our purpose was to compare the frequency and intensity of FD and its associations with symptom distress and quality of life (QOL) in these patients in France and the U.S. Materials and Methods: In this secondary analysis of two cross‐sectional studies, we assessed data on 292 patients who received cancer care at a public hospital or a comprehensive cancer center in France (143 patients) or the U.S. (149 patients). Outpatients and hospitalized patients over 18 years of age with advanced lung or breast or colorectal or prostate cancer were included. Diagnosed cognitive disorder was considered a noninclusion criterion. Advanced cancer included relapse or metastasis or locally advanced cancer or at least a second‐line chemotherapy regimen. Patients self‐rated FD and assessed symptoms, psychosocial distress, and QOL on validated questionnaires. Results: The average patient age was 59 years, and 144 (49%) were female. FD and high intensity were reported more frequently in U.S. patients than in French (respectively 129 [88%] vs. 74 [52%], p  < .001; 100 [98%] vs. 48 [34%], p  < .001, ). QOL was rated higher by the U.S. patients than by the French (69 [SD, 18] vs. 63 [SD, 18], p  = .003). French patients had more psychological symptoms such as anxiety (8 [SD, 4] vs. 6 [SD, 5], p  = .008). Associations were found between FD and U.S. residence, FD and single status (0.907, p  = .023), and FD and metastasis (1.538, p  = .036). In contrast, negative associations were found between FD and older age (−0.052, p  = .003) and FD and France residence (−3.376, p  = .001). Conclusion: Regardless of health care system, FD is frequent in patients with advanced cancer. U.S. patients were more likely to have FD than French patients but reported better QOL. Further research should focus on factors contributing to FD and opportunities for remediation. Abstract : Cancer patients and their families often must make financial adjustments related to the costs of treatment. This articles explores the effects of financial distress on overall quality of life, focusing on the differences in results in patients treated within the different health care systems of the U.S. and France.